Lung cancer 4: Chemotherapy for non-small cell lung cancer: the end of the beginning. Issue 4 (1st April 2003) - Cullen, M
Abstract : The development of chemotherapy for NSCLC over the last 20 years is reviewed, particularly with regard to its palliative effects. New "fourth generation" agents designed to inhibit specific biological pathways thought to be crucial to tumour growth give cause for optimism in the future treatment of NSCLC.